INVESTIGATIONS ON SEWAGE TREATMENT PROCESS USING COMBINED BIO-OXIDIZERS - V. N. Jaromsky; E. I. Mihnevich (Наука и техника)
The paper presents results of investigations on process of aerobic waste water treatment with combined bio-oxidizers at milk processing enterprises. It has been shown that attached biocenosis, free-floating biocenosis and also bio-module rotation frequency  have exerted a significant influence on the process of an aerobic sewage treatment. It has been established that combined bio-oxidizers can be used for cleaning high concentrated waste water at the enterprises of food industry.